STRATEGY FOR FORMING AN ARABIC LANGUAGE ENVIRONMENT IN AL QODIRI ISLAMIC SENIOR HIGH SCHOOL 1 JEMBER - Qudsi, Muhowwifullah Amin; Maskud, Maskud; Rosyid, Abdul (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
This study aimed to analyze models of the Arabic language environment formation to increase the ability of language learners in Al Qodiri Islamic Senior High School 1 Jember. This research method was qualitative. The research was conducted at Al Qodiri Islamic Senior High School 1 Jember. Research respondents were 245 students of boarding Islamic Senior High School that consisted of 170 females and 73 males. The data collection method used participant observation instruments and interviews. Both of these instruments were used to get data about the models of the Arabic language environment formation to increase the language skills of students in Islamic Senior High School. Steps of Data analysis techniques were collecting data, reducing data, presenting data, and making a conclusion. The results showed that the model of the formation of the Arabic language environment consisted of the visual environment, audio environment, and the audiovisual environment. This model was able to overcome the difficulties of students in acquiring Arabic. This model of the Arabic language environment provides direct and natural Arabic mastery. Qualitative analysis results showed that the Arabic environment was able to increase students’ language skills of Al Qodiri Islamic Senior High School 1 Jember.